Realization of the EU's Cohesion Policy in Health Care in the Visegrad Group Countries in the Perspective 2014-2020 - Holecki, Tomasz; Kowalska-Bobko, Iwona; Fraczkiewicz-Wronka, Aldona; Wegrzyn, Maria (Frontiers in Public Health, 2020)
A key objective of the European Union is to strengthen regional cohesion by addressing development disparities, particularly by targeting less-favored regions (1). Initiatives related to leveling development differences in the field of health care are recognized as a one of priorities in the European Union. Therefore, when implementing cohesion policy, decisions have been made to mobilize structural funds for sectoral activities. The aim of this paper is to present the European Union's cohesion policy in the field of health care and to indicate the most important actions of the implemented programmes/projects in selected countries: Poland, the Czech Republic, the Slovak Republic and Hungary—the Visegrad Group–VG4—in the period of 2014–2020. Analysis covers programmes, funding sources, and activities undertaken in achieving cohesion policy objectives in health care in the VG4.